Ethnobotanical Survey of Medicinal Plants in Ruhuli Village, Tangail, Bangladesh - Sadia, Halima Tujj; Amir , M Julfiqar Sultanul; Ashrafuzzaman, M (Journal of the Bangladesh Agricultural University, 2025)
A study was conducted to explore the diversity and uses of local medicinal plants in the village of Ruhuli, Gobindashi union, Bhuapur upazila, Tangail district of Bangladesh. Data were collected through semi-structured questionnaires, group discussions, and face-to-face interviews with pre-identified informants. This paper documented these medicinal plant species along with their local name, botanical name, family name, parts used, and traditional usage of application. A total of 104 medicinal plant species from 91 genera and 49 families were documented. The Cucurbitaceae, Liguminosae, and Zingiberaceae families each contributed the highest number of species (six), followed by Asteraceae, Lamiaceae, and Rutaceae with five species each. Acanthaceae, Combretaceae, and Malvaceae were represented by four species each, while twenty-seven families were represented by a single species. The most species-rich genera were Terminalia and Curcuma, each with three species, followed by Amaranthus, Citrus, Hibiscus, Justicia, and Senna, each with two species. The remaining 85 genera are represented by a single species. The most frequently used plant parts were leaves (30%) and fruits (16%), with decoction being the most common preparation method (50 species). These plants were primarily used to treat gastrointestinal disorders (58 plant species), followed by urogenital diseases (23 plant species). The other diseases addressed by these plants included cardiovascular; dermatological; ENT, eye and hair; helminthiasis; hematological; infectious; inflammatory; Glandular; Respiratory; Sexual and neurological conditions. The local people used these species in the treatment of 88 different diseases of human being. Frequency of citation (FC), relative frequency of citation (RFC), use value (UV), use report (UR) were used for identification of the popularity level, efficiency medicinal importance of the plants among the community. J Bangladesh Agril Univ 23(3): 311–321, 2025